Foreign policy analysis - Brummer, Klaus, 19..-; Oppermann, Kai (Oxford University Press., 2024)
'Foreign Policy Analysis' puts theoretical approaches front and centre without neglecting the rich connection with international relations theories. This book challenges Western-centric perspectives on foreign policy analysis and reflects the rise of non-Western scholarship in the field